Telegram analytics - Tucci, Giulia (2025)
Telegram Analytics is an open, lightweight workflow that turns public conversations on Telegram – a key digital space for real-time debate – into structured insights for issue mapping. Paired with TeleCatch for easy data collection from public channels, it quickly organizes messages and surfaces themes, actors, and timelines, producing clear tables and simple visuals your team can read or plug into common analysis tools.